Pelatihan Investasi Reksa Dana Syariah untuk Pelajar sebagai Investor Pemula - Angela Dirman; Waluyo Waluyo; Annisa Hakim Zamzami (LPMP Imperium, 2025)
The increasing prevalence of online gaming among students, often linked to online gambling sponsorships, has raised concerns about financial literacy among young individuals. The Indonesian Teachers Association (PGSI) reported that 12,000 students were involved in online gaming with gambling sponsorship, highlighting the urgent need for financial education. Lack of financial literacy makes students vulnerable to the allure of quick wealth promised by online gambling platforms. Therefore, introducing investment knowledge, particularly in Sharia mutual funds, is essential to prevent financial mismanagement. This community engagement program was conducted at Al-Ihsan Vocational High School on February 1, 2024 with 91 participants. The program consisted of two sessions: the first session covered financial investment education, while the second session involved interactive discussions and hands-on practice in online Sharia mutual fund transactions. The objective was to equip students with fundamental investment knowledge, enabling them to make informed financial decisions. By providing structured financial education and training, this initiative aims to foster a generation of financially literate young investors. The long-term goal is to empower students to manage their finances wisely, mitigating the risks associated with online gambling and enhancing their economic resilience.